TINDAK TUTUR KOMISIF PADA DEBAT PERTAMA CALON PRESIDEN PERIODE 2024 DAN RENCANA PELAKSANAAN PEMBELAJARAN DI SMA - Muhamad Rizki Riadi; Dase Erwin Juansah; Ade Anggraini Kartika Devi (Universitas Batanghari, 2025)
Commissive speech acts demand trustworthiness and seriousness from speakers in carrying out what they have said. This commissive speech act is not only found in everyday life, but can also be found in debate dialog. The purpose of this study is to identify and describe the form and function of commissive speech acts in the first debate of 2024 presidential candidates. This research is a descriptive qualitative type with data collection techniques using listening and note-taking techniques. At the data analysis stage, the researcher tries to compare, classify, and describe the data that has been found. Based on the analysis, the results obtained 24 data of commissive speech acts from the speech at the first debate of the 2024 Presidential Candidates, namely commissive illocutionary speech acts swearing there is 1 data, commissive illocutionary speech acts threatening obtained 0 data, commissive illocutionary speech acts expressing ability there is 1 data, commissive illocutionary speech acts vowed (vowed) obtained 6 data, and commissive illocutionary speech acts offering there is 1 data. The data found can be applied in Indonesian language learning in SMA Class XI, on argumentation text material as an example of text in fact and opinion sentences.